Spatial variability of soybean straw distributed at harvest and its relationship with the final stand of black oats - Tagliari-Balestrin, Júlio (2021)
The objective of this work was to evaluate the effect of spatial variability straw distribution on soybean harvest in the emergence of black oats in no-tillage system. The experiment was carried out in an agricultural area of ​​2.6 ha, being evaluated the amount of soybean straw (kg ha-1) distributed by the harvester, and the final stand of black oats (plants m-2). A 20-point sampling grid was used, 10 points in the center of the harvester and the other 10 at the ends. At the points in the center of the harvester, the amount of straw varied from 6,424 to 12,000 kg ha-1 ( = 8,788 ± 1,669 kg ha-1), while the final stand of black oat plants ranged from 165 to 212 plants m-2 ( = 191 ± 14 plants m-2). In the points related to the ends, the amount of straw reduce to 1,697 to 3,394 kg ha-1 ( = 2,448 ± 588 kg ha-1) and the final stand of black oat increase to 267 to 306 plants m-2 ( = 285 ± 13 plants m-2), that is, a reduction of 72.14% in the amount of straw and an increase of 49.21% in the stand. The variables analyzed showed a strong, negative and significant correlation (r = - 0.887; P ˂ 0.05), therefore, the combine used in this study distributes the uneven straw, and this action affects the final stand of black oats.